SUPPORTIVE ANTENATAL CARE FOR EMOTIONAL WELL-BEING (SAFE) EDUCATION TO PREVENT POSTPARTUM BLUES: A PRISMA-BASED SYSTEMATIC LITERATURE REVIEW OF RANDOMIZED AND QUASI-EXPERIMENTAL STUDIES (2021-2025) - Beta Karlistiyaningsih; Sri Rejeki; Machmudah; Edy Soesanto; Ernawati (Pena Cendekia Insani, 2026)
Postpartum blues is a common emotional disturbance during the early postpartum period and may progress to postpartum depression if left unmanaged. SAFE education has emerged as a non-pharmacological approach to improve maternal emotional preparedness. This study systematically evaluated the effectiveness of SAFE education in preventing postpartum blues through a Systematic Literature Review (SLR). Literature searches were conducted in PubMed, Scopus, and Google Scholar for studies published between 2021 and 2025. Following PRISMA 2020 guidelines, 309 records were initially identified from three electronic databases. After the removal of 102 duplicate records, 207 unique articles underwent title and abstract screening. Of these, 112 full-text articles were assessed for eligibility, and 12 studies involving approximately 1,900 participants fulfilled all predefined inclusion criteria and were included in the final qualitative synthesis. The findings consistently demonstrated that SAFE education reduced postpartum blues symptoms, anxiety, stress, and mild depressive symptoms while improving maternal knowledge, self-efficacy, emotional preparedness, coping skills, and perceived social support. Due to substantial heterogeneity in study designs, interventions, and outcome measures, a narrative synthesis was performed instead of a meta-analysis. Overall, SAFE education appears to be a promising antenatal intervention for promoting maternal mental health and reducing the risk of postpartum blues.